Mail order wife - Botko, Huck; Gurland, Andrew; Yuan, Eugenia; Martinez, Adrian; Visual Entertainment (Firm). (Universal City, Calif. Distributed by D' Concorde recording corp., 2005)
bachelor looking for a wife agrees to be filmed for a mock documentary as he gets a mail order bride. His new wife is convinced he wants a maid more than anything. A dark comedy about how hard it is to find love, especially from a catalogue.
Director of photography, Luke Geissbuhler ; editor, Kevin Napier ; music, Mark Wike.
Andrew Gurland, Eugenia Yuan, Adrian Martinez ; casting by Lori Eastside ; music supervisor Mark Wike ; costume designer Jennifer Galvelis ; Production designer Jon Nissenbaum ; editor Kevin Napier ; Director of photography Luke Geisbuhler ; executive producers David Bartis, Doug Liman, Bo Hyde, Bobby Sheng
MPAA rating: R; for language, and some disturbing sexual material.
DVD, region 1, widescreen (1.78:1) presentation; Dolby Digital 5.1.
Winner of the Best Independent Feature Film of the 2005 Santa Barbara Film Festival.
Keywords: Mail order brides -- Drama; Foreign spouses -- Drama; Feature films; Queens (New York, N.Y.) -- Drama